2003
DOI: 10.1038/sj.npp.1300139
|View full text |Cite
|
Sign up to set email alerts
|

A Confirmatory Study on the Mechanisms Behind Reduced P300 Waves in Depression

Abstract: A single-trial analysis of event-related potentials (P300) of 21 depressives was performed in comparison with matched controls. The purpose was to confirm previous results revealing an overall reduction of the single-trial P300 amplitude in depression despite fewer elicited single-trial P300 waves in schizophrenics. The result of the present study is in line with our previous investigation implicating a general reduced P300 amplitude on single trials of depressive patients. Therefore, it appears possible to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
40
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 17 publications
9
40
0
2
Order By: Relevance
“…Results of our study are in concordance with most studies in classic oddball tasks reporting N2b and P3b deficits (amplitude reduction and latency prolongation) in bipolar disorder (Gangadhar et al 1993;Muir et al 1991;O'Donnell et al 2004;Roschke and Wagner 2003;Salisbury et al 1999;Strik et al 1998). The bipolar patients have shown disturbances on the later stages when attentional and working memory mechanisms indexed by N2b and P3b are engaged (O'Donnell et al 2004).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Results of our study are in concordance with most studies in classic oddball tasks reporting N2b and P3b deficits (amplitude reduction and latency prolongation) in bipolar disorder (Gangadhar et al 1993;Muir et al 1991;O'Donnell et al 2004;Roschke and Wagner 2003;Salisbury et al 1999;Strik et al 1998). The bipolar patients have shown disturbances on the later stages when attentional and working memory mechanisms indexed by N2b and P3b are engaged (O'Donnell et al 2004).…”
Section: Discussionsupporting
confidence: 92%
“…The presence of a P3b reduction in manic-depressive patients is equivocal. Some studies have shown a reduction in amplitude (Gangadhar et al 1993;Roschke and Wagner 2003), but others have failed to find a reduced P3b amplitude (Hansenne et al 1994). P300 amplitude was reduced in bipolar psychotic disorder (Muir et al 1991), and in depressed patients (Bange and Bathien 1998;Salisbury et al 1998Salisbury et al , 1999Santosh et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it has been reported that major depression is related to P300 amplitude reduction (Anderer et al, 2002;Blackwood et al, 1987;Gangadhar et al, 1993;Roschke and Wagner, 2003) and one could argue that this could have contributed to the amplitude reduction observed in participants with OCD compared to the GTS and control groups. However, covariance analysis revealed that group differences remained statistically significant after depressive symptoms had been introduced as a covariable.…”
Section: Possible Influences Of Confounding Variablesmentioning
confidence: 99%
“…The P300 ERP is thought to reflect the degree to which attention is allocated and incoming information is processed and incorporated into working memory [Donchin et al, 1986;Polich and Herbst, 2000]. Numerous studies have shown that low amplitude P300 is associated with psychopathology including MD [Bruder et al, 1995;Roschke and Wagner, 2003], alcoholism [Begleiter et al, 1984;Hill and Steinhauer, 1993;Reese and Polich, 2003], impulsivity and antisocial personality disorder [Iacono et al, 2002;Justus et al, 2001], and schizophrenia [Higashima et al, 2003;Jeon and Polich, 2003]. Only a few studies have looked at the relationship between anxiety and P300.…”
Section: Introductionmentioning
confidence: 99%